Fuzzy analytical hierarchy process for analysing the factors that influence the career choices of graduate students at UiTM Perlis / Khairu Azlan Abd Aziz ... [et al.] - Abd Aziz, Khairu Azlan; Wan Daud, Wan Suhana; Mohd Idris, Mohd Fazril Izhar; Saimuddi, Salsabila (UiTM Cawangan Perlis, 2024)
There are various types of careers that graduated students can pursue today. However, the career selection could be quite confusing and challenging, due to some factors such as parental and academic influences, personal interest and work environment. This study is aimed to rank the main factor and sub-factor that influence the students’ career choices of graduate students at UiTM Perlis. Interviews are conducted in obtaining the input for the study. Based on the input obtained, the study utilized the approach based on Saaty’s scale and fuzzy analytic hierarchy process (AHP). The factor that has the highest value of the normalized weight is that most influences factor, which is the personal interest factor. For sub-factors, workplace is the most influential factor, while the sub-factor with the least influence is safety under the parental factor, which is also the least ranked of the factors influencing students' career choices.